Faktor Determinan Strategi Bisnis Usaha Kopra Putih di Katumbangan Lemo - Noor Hasana Hakim; Putra, Nur Astaman (Journal of Economic Education and Entrepreneurship Studies, 2023)
This research aims to determine the business determinants of white copra in katumbangan lemo, polewali mandar regency, west sulawesi. The method used in this research is a qualitative method, namely field research, then the results are analyzed descriptively and arranged systematically. The research results show that the determinant factors consist of two things. First, the supporting factors are: (1) investors’ interest in profit sharing in this whitw copra business, (2) farmers’ capital needs which increase during the harvest process, (3) labor intensive, and (4) farmers’ mindset regarding differences prices between white copra managers and businessman who are intermediaries. Second, the inhibiting factors are: (1) many farmers choose to take out loans from banks, (2) capital turnover is not smooth, and (3) white Kopra is very dependent on sungliht.